2021
DOI: 10.3390/vaccines9101067
|View full text |Cite
|
Sign up to set email alerts
|

Potential Adjuvant Therapeutic Effect of Lactobacillus plantarum Probio-88 Postbiotics against SARS-COV-2

Abstract: In response to the ongoing COVID-19 pandemic, the global effort to develop high efficacy countermeasures to control the infection are being conducted at full swing. While the efficacy of vaccines and coronavirus drugs are being tested, the microbiome approach represents an alternative pathophysiology-based approach to prevent the severity of the infection. In the current study, we evaluated the action of a novel probiotic Lactobacillus plantarum Probio-88 against SARS-COV-2 replication and immune regulation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Similar results were also reported by Rather et al [ 16 ], where they observed that L. plantarum isolated from Kimchi also has the antiviral activity. One of our previous studies recently showed that L. plantarum inhibits SARS-CoV [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also reported by Rather et al [ 16 ], where they observed that L. plantarum isolated from Kimchi also has the antiviral activity. One of our previous studies recently showed that L. plantarum inhibits SARS-CoV [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, probiotics are live microorganisms that benefit the host, similar to the gut microflora [ 4 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and are known to survive in gastric and bile acid in the gastrointestinal tract [ 23 , 24 ]. Various probiotic LAB strains have been reported in fermented foods and dairy products [ 1 , 2 , 14 , 16 , 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, LABs from camel milk are less explored for their health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these postbiotics can act as a “blocker” of viral ss-RNA during its replication. This strain and/or its postbiotic substances can be used as an integrative approach, along with a vaccine, to contain the spread of SARS-CoV-2 and, most importantly, its variants [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…GM modulation can change humans’ metabolism and the availability of energy sources for a better sport performance [ 7 ]. For example, an increased abundance of Veillonella in our gut, able to metabolize lactic acid to propionate, significantly increases animals’ physical performance [ 106 ]. Similarly, enteral administration of propionic acid leads to similar results [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation